2005
DOI: 10.1021/ie050685h
|View full text |Cite
|
Sign up to set email alerts
|

Approach Suitable for Screening Estimation Methods for Critical Properties of Heavy Compounds

Abstract: A simple theoretical-based correlation of the ratio of the critical temperature to the critical pressure (T c /p c ) as a function of the van der Waals surface area (Q w ) has been previously developed based on an extensive database of critical data published prior to 1996. The final equation was the following: T c /p c ) 9.0673 + 0.43309(Q w 1.3 + Q w 1.95 ) where T c is the critical temperature in kelvin and p c is the critical pressure in bar. This correlation is further validated here based on recent exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
5
16
0
Order By: Relevance
“…It is clear that the generalized TcPc relation proposed could not be regarded as an alternative to GC methods, as it is essentially an interrelationship between two critical constants. Nonetheless, its universal applicability that has been validated for 1,589 compounds of low to high molecular weights and a wide variety of polarities ensures its utility in comparing and testing existing and under‐development GC methods 29 . Aside from this important screening function, the general trend of compounds belonging to a specific family could also be determined, with the possibility of interpolation and extrapolation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that the generalized TcPc relation proposed could not be regarded as an alternative to GC methods, as it is essentially an interrelationship between two critical constants. Nonetheless, its universal applicability that has been validated for 1,589 compounds of low to high molecular weights and a wide variety of polarities ensures its utility in comparing and testing existing and under‐development GC methods 29 . Aside from this important screening function, the general trend of compounds belonging to a specific family could also be determined, with the possibility of interpolation and extrapolation.…”
Section: Methodsmentioning
confidence: 99%
“…Taking a cue from, and concurrently substantiating this supposition, several studies have indicated that the TcPc ratio can be correlated much better than either property individually 23‐25 . In particular, expanding upon the study by Bae et al, 2 Kontogeorgis and co‐workers have advocated in a series of publications 26‐29 that it is possible to relate the TcPc ratio of high molecular weight compounds to a single parameter, that is, the compound's normalized van der Waals surface area ( Q ) given by Bondi 30 and reported in the UNIFAC GC tables 31 as: TcPc()normalK.bar1=9.0673+0.43309()Q1.3+Q1.95 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it is not possible to compare the values estimated by us with those of other authors. Still, an evaluation of the reliability of the properties prediction can be made applying the generalized semitheoretical expression advocated by Zbogar et al (2006), namely:…”
Section: Simulation Of Whole Extraction Curves With Model IIImentioning
confidence: 99%
“…Due to molecular packing (which exists in the liquid as well as the solid state), this co-volume is expected to be higher than the molecular (or vdW) volume. The following equation can be used for screening estimation methods: [19][20][21] T c P c ¼ 9:0673 þ 0:433 09 Q 1:3 w þ Q 1:95 The reason for including b ¼ 1:41 V w in Table 3.4 lies in the well-accepted picture for the liquid state that each molecule has about 10 neighbor molecules, i.e.…”
Section: Pure Compoundsmentioning
confidence: 99%